Profitability and Feasibility Analysis of Sand Lobster (Panulirus homarus) Farming in Jerowaru District East Lombok Regency - Aneswari, Yuansa; Ibrahim, Ibrahim; Nursan, Muhammad (Jurnal Biologi Tropis, 2022)
Jerowaru District is one of the areas in East Lombok Regency which has enormous potential in the aspect of developing lobster cultivation. Especially the cultivation of sand lobster (Panulirus homarus) which is supported by geographical conditions, public interest, and also from the government. This study aims to: (1) analyze the profitability of sand lobster (Panulirus homarus) farming, (2) analyze the feasibility of sand lobster (Panulirus homarus) farming, (3) find out the constraints on sand lobster (Panulirus homarus) farming in Jerowaru District, East Lombok Regency. The method used in this study is a descriptive method with the unit of analysis used is the sand lobster (Panulirus homarus) farming in Jerowaru District, East Lombok Regency. The results showed that: (1) Sand lobster farming in Jerowaru District, East Lombok Regency has a high level of profitability or a high level of profit, the income generated is Rp. 23,189,000 with a total production of Rp. 14,015,000 so that the return value is obtained. Of Investment (ROI) of 165.45%. (2) The sand lobster cultivation business in Jerowaru District, East Lombok Regency is feasible because the R/C ratio value obtained is greater than 1 (2.65 > 1) and the B/C ratio is greater than zero (1.65 > 0). (3) Constraints faced by sand lobster respondents in Jerowaru District, East Lombok Regency, namely weather constraints, disease, post-harvest, selling prices, feed, damaged nets and theft.